Comparison analysis of wireless network audits using open source tools - Islam, Nuzhat Nuary; Zareen, Fahmida (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electronics and Communication Engineering, 2014.